Twenty-one new species of Omaliini from the Papuan Region (Coleoptera: Staphylinidae: Omaliinae), with diagnostic and faunistic notes on some species of the genus Paraphloeostiba Steel, 1960 - Shavrin, Alexey V. (Zootaxa, 2024)
New taxonomic, diagnostic and faunistic data for 26 species of Nipponophloeostiba Watanabe, 1962 (one species), Paraphloeostiba Steel, 1960 (23 species) and Xanthonomus Bernhauer, 1926 (two species) of the tribe Omaliini McLeay, 1825 of the Papuan Region (Indonesia (Western New Guinea), Papua New Guinea and Solomon Islands) are provided. Twenty-one new species are described and illustrated: Nipponophloeostiba hornabrooki sp. n., Paraphloeostiba assimile sp. n., P. attenuata sp. n., P. barclayi sp. n., P. betlephila sp. n., P. coprophila sp. n., P. latissima sp. n., P. okapensis sp. n., P. rufula sp. n., P. steeli sp. n., P. telnovi sp. n. and Xanthonomus thayerae sp. n. from Papua New Guinea, P. atramentaria sp. n., P. iriana sp. n., P. margineguttata sp. n., P. pilosa sp. n., P. riedeli sp. n., P. vitiosa sp. n., and X. guineensis sp. n. from Western New Guinea (Indonesia), and P. guadalcanalensis sp. n. and P. penelopeae sp. n. from Solomon Islands. Paraphloeostiba coriacea (Cameron, 1952) and P. rhopalocera (Cameron, 1928) are redescribed and illustrated. The male of P. papuana (Cameron, 1931) and females of P. conjuncta Shavrin, 2023 and P. coriacea are described and illustrated for the first time. Keys for Nipponophloeostiba Watanabe, 1962, Xanthonomus Bernhauer, 1926, and the Papuan species of the genus Paraphloeostiba are provided. Distributional maps of Xanthonomus and Nipponophloeostiba, and P. coriacea, P. gayndahensis (MacLeay, 1873) (for New Guinea) and P. papuana are given. Paraphloeostiba conjuncta, P. coriacea, P. gayndahensis and P. papuana are recorded from Indonesia (Western New Guinea) for the first time.